Cefotaxime-Resistant Enterobacteriaceae Isolates from a Hospital in Warsaw, Poland: Identification of a New CTX-M-3 Cefotaxime-Hydrolyzing β-Lactamase That Is Closely Related to the CTX-M-1/MEN-1 Enzyme - Gniadkowski, Marek (American Society for Microbiology, 1998)
A group of cefotaxime-resistant Citrobacter freundii and Escherichia coli isolates were collected by a clinical laboratory in a hospital in Warsaw, Poland, in July 1996. Detailed analysis has shown that all of these produced a β-lactamase (pI, 8.4) belonging to the CTX-M family, one of the minor extended-spectrum β-lactamase families with a strong cefotaxime-hydrolyzing activity. Sequencing has revealed that C. freundii isolates produced a new CTX-M-3 enzyme which is very closely related to the CTX-M-1/MEN-1 β-lactamase, sporadically identified in Europe over a period of 6 years. Amino acid sequences of these two β-lactamases differ at four positions: Val77Ala, Asp114Asn, Ser140Ala, and Asn288Asp (the first amino acid of each pair refers to CTX-M-1/MEN-1 and second refers to CTX-M-3). The partial sequence of the E. coli CTX-M gene was identical to the corresponding region of bla(CTX-M-3), but a transconjugant of the E. coli isolate expressed higher levels of resistance to β-lactams than did C. freundii transconjugants. These resistance differences correlated with differences in plasmid DNA restriction patterns. Our results suggest that CTX-M genes have been spread among different species of the family Enterobacteriaceae in the hospital and that the CTX-M-3-expressing C. freundii strain causing routine urinary tract infections has been maintained for a relatively long time in the hospital environment.